THE DEVELOPMENT OF CREATIVITY IN CHILDREN STORY WRITING FOR INDUSTRY MORAL AND CULTURE BASED ON CREATIVITY NATION - Zulela MS (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The development of this research aims to produce a set of models of teaching elementary school children to write stories that integrate approaches, methods, instructional media in developing creative writing children stories among elementary school students. In particular, this research is expected to produce outputs (products) in the form:1) a model in the development of primary school children to write stories, 2) examples Subjects who can lead the development of writing skills of primary school children's story, 2). Examples of children's story of the development of elementary school students, were excavated from the real experience of the students, the which can be built into a part of the creative industries are rooted in ideas of elementary school students.This research trying to empower the potential that exists in elementary school students. The second stage of the research that will come in the learning models will be implemented a to write stories (experimental) in elementary school, and the results will be applied in the form of models of teaching materials in writing stories and examples of stories. If this research can be continued into the third stage will be Followed by a revision of the results of children's stories written by elementary school students. Furthermore, mass production in cooperation with publishers and Obtain intellectual property rights Keywords: Writing, Children's Stories, Copyright